Inequities and factors associated with gender and disability in NTD-endemic communities in Benin and Côte d'Ivoire: an intersectional approach to interventions - Ginette Victoire Senami Gandigbe; Zinsou Franck Mignanwande; Yévèdo Borel Tossou; Karine Lucrèce Marie Codjo-Seignon; Sonagnon Inès Elvire Agbo; Fifamin Noël Christelle Gbaguidi; Sèdjro Gimatal Esaï Anagonou; Fernand Aimé Guedou; Mark Nichter; Cristina Juan Jimenez; Roch Christian Johnson; Roch Christian Johnson; et al. (Frontiers in Global Women's Health)
IntroductionGender inequity among people with disabilities (PWD) is a complex issue influenced by a combination of socioeconomic, cultural, political, and institutional factors. Women with disabilities often experience double discrimination, increasing their vulnerability. These exacerbate their already difficult health and living conditions. This study aimed to explore the factors associated with gender inequities among PWD in Benin and Côte d'Ivoire, and to design and implement tailored interventions to address these inequities.MethodThis intervention-oriented operational research, employing a mixed-methods approach (quantitative and qualitative), targeted 841 PWD and 90 community members. Initially, records from various centers managing Neglected Tropical Diseases (NTDs) in the study areas were reviewed. All PWD listed in the registers and residing in the community, as well as other community members, were included. Data on socio-demographic and socioeconomic and clinical factors were collected using an interview guide and an observation grid. Quantitative data were analyzed using SPSS version 25 (alpha = 5%), while qualitative data were processed through triangulation, categorized, cross-tabulated, and synthesized by theme, hypothesis, and indicator. A subset of PWD facing barriers to accessing education, training, income-generating activities, or healthcare was selected for intervention.ResultsThe median age was 38 years (IQR = 22–52). Among the 841 PWD, 497 were men and 344 were women (sex ratio = 1.45). Univariate analysis revealed significant associations (p = 0.000) between gender disparities and marital status, monthly income, education level and occupation type. Multivariable analysis identified three factors strongly associated with gender disparities (p = 0.000): marital status, monthly income, and profession. Interventions were designed to address these factors and included vocational training, medical care, and educational or professional scholarships. These measures collectively improved the living conditions of PWD and helped raise awareness among those in their immediate environment, fostering social integration and reducing self-stigmatization.ConclusionThis study provides a deeper understanding of the inequalities that PWDs face in Benin and Côte d’Ivoire. It highlights the need to adopt intersectional approaches in policies and practices to effectively address the multiple forms of discrimination faced by women and girls with disabilities, promoting their inclusion and protection in all areas of society.